Exploration of Micro-Finance Banking Policies and Strategies for Poverty Reduction in Nigeria - Musa, Umar Farouk; Abubakar, Inuwa Baba (Australian Finance & Banking Review, 2017)
Poverty is one of the socioeconomic challenges bed evilling many families, particularly the northern states of Nigeria. This study applied qualitative research paradigm and generated the perceptions of informants via convinience sampling. We analyzed the data through thematic, narrative and interactional apparoach. Our objective is to explore microfinance institutions strategic policies for poverty reduction and recommend to policy makers. The results exposed that micro financial institutions were classified into formal, informal, development and those with mortgage outlook.The Central Bank of Nigeria issue the certificate for authorization, the licensing and ownership. The Paid-up capital requirements, the permissible and acceptance of deposits, savings from individuals, groups and associations were the policies which propel these institutions. The non-permissible policies are restrictions on acceptance of public sector deposits. The study identified inadequate supervsions and loans defaults, poor infrasturectural facilities in rural areas, pitiable communication and derisory banking experience among the poor and low income earners, limited standardization and operating system as well hampered their services in the quest to mitigate poverty in the study area.The re-capitalization, efffective regulatory control via financial control, regularly supervision, checks and balances. Capacity building programs and Proper staffing.Provision of appropriate business model; strategies and creation of awareness. The provision of door to door banking marketing awareness, establishment of financial literacy; consumer protection programs and Provision of non-interest banking programs were perceived to overcome the perils of these institutions respectively. The study recommended for establishment of Islamic financial institutions and Takaful insurance scheme.